Religion as system, performance and stock of knowledge : towards an appropriate social-theoretical perspective on the societal significance of religion in South Africa - Muller, H. P.(Hans Peter),1962- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D. Phil.) -- University of Stellenbosch, 1997.